PENGARUH PERSEPSI TERHADAP MINAT ETNIS TIONGHOA KOTA BANDA ACEH TERHADAP PERBANKAN SYARIAH (Equilibrium: Jurnal Ekonomi Syariah, 2016)
This study was conducted to know the interest of Chinese ethnic community on Sharia banking. It focused on the factors influencing the perceptions and interests of Chinese ethnic, how perceptions of Chinese ethnic to Sharia banking, and how the influence of perception factors on the interests of Banda Aceh Chinese ethnic on sharia banking. This study used quantitative methods involving 100 Chinese ethnic respondents in Banda Aceh. The result showed that perception factors involving individual variables, objects and environments have a correlation coefficient which is close to the interest 86.1%, and the coefficient of determination also shows that 74.1% of interest is influenced by those three variables. The most significant variable affecting interest is the environment variable with regression coefficient value 1,321. It means that individual variables, objects and environments affect the Chinese ethnic in choosing sharia banks.